13-2(3x-1)=18-4(2x+1)+3x

Simple and best practice solution for 13-2(3x-1)=18-4(2x+1)+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13-2(3x-1)=18-4(2x+1)+3x equation:



13-2(3x-1)=18-4(2x+1)+3x
We move all terms to the left:
13-2(3x-1)-(18-4(2x+1)+3x)=0
We multiply parentheses
-6x-(18-4(2x+1)+3x)+2+13=0
We calculate terms in parentheses: -(18-4(2x+1)+3x), so:
18-4(2x+1)+3x
determiningTheFunctionDomain -4(2x+1)+3x+18
We add all the numbers together, and all the variables
3x-4(2x+1)+18
We multiply parentheses
3x-8x-4+18
We add all the numbers together, and all the variables
-5x+14
Back to the equation:
-(-5x+14)
We add all the numbers together, and all the variables
-6x-(-5x+14)+15=0
We get rid of parentheses
-6x+5x-14+15=0
We add all the numbers together, and all the variables
-1x+1=0
We move all terms containing x to the left, all other terms to the right
-x=-1
x=-1/-1
x=1

See similar equations:

| -16=|-4k| | | 26=38-x | | 9–2f=39 | | 5x2−3x-7=1 | | -2r-r=9 | | 5(x-6)=2(x+3$ | | F(-2)=9-3x | | 4x-9/7-1=6/5x | | 9–2f=3 | | (4-3x)(2+x)= | | x-88/9=3/5 | | 3(3x-2)-2x=15 | | -7+5u=13 | | 2(4i+2)=4i-12(i-1) | | 5/y+2=2/y+2+3 | | 16/4=y/4 | | 6w-60=2w | | 3k-16=-4 | | 10x-57=47 | | 5x+9=-93 | | 5^3x+1=29 | | 3s+10=10s-53 | | 4x–313=-2x+5≥7 | | 5x=9=-6 | | 1/3+y=-4 | | M/3+m6=8 | | 4(-7x+2)=64 | | 5x2−4x−7=1−x | | 15-1/2x2=x | | 4x=18-(-4) | | `-12=7-h | | 34=–(m+3) |

Equations solver categories